Product Life Cycles in Corporate Finance - Hoberg, Gerard; Maksimovic, Vojislav (Review of Financial Studies, 2022)
We develop a novel 10-K text-based model of product life cycles and examine firm investment policies. Conditioning on the life cycle substantially improves the power of q to explain investment and reveals a natural ordering of investments over the life cycle. While R&D and CAPX sensitivity are high early in the cycle, acquisitions arise as products mature, and divestitures and product extension investments arise as products decline. q-sensitivities that condition on the life cycle can vary by as much as 400% from traditional sensitivities. The life cycle framework further reveals an enriched relationship between competition, investment, and corporate profits. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.